2007
DOI: 10.1007/bf02686028
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles analysis of the growing rat liver in response to different zinc status by cDNA microarray analysis

Abstract: The effects of zinc on growing rats were characterized using the dietary zinc-deficient (ZD) and Zinc-overdose (ZO) models. Zinc deficiency had negative effects on the host final body weight and liver zinc content, whereas zinc overdose had positive effects. In order to identify the molecular changes in the liver responding to dietary zinc status, cDNA microarrays were used to analyze the expression pattern of 9753 genes in the livers of rats fed ZD and ZO diet for 6 wk, compared with zinc-adequate ZA. The mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…When rats were fed a high zinc diet (347.50 mg Zn/kg basis diet, compared to a normal diet level of 35.94 mg Zn/kg basis diet), up-regulated genes included those involving carbohydrate metabolism (e.g. alcohol dehydrogenase ( Adh5) , pyruvate dehydrogenase kinase 4 ( Pdk4) , aldolase C ( Aldoc) ) (Sun et al, 2007). Another study utilizing intratracheal instillation of zinc sulfate in rats was focused on changes in cardiac gene expression, where up-regulation of respiratory/mitochondrial function genes (pyruvate dehydrogenase kinase 4 ( Pdk4 ), acylcoenzyme A dehydrogenase ( Acadvl )), injury/stress response (heme oxygenase 1 ( Hmox1) , tissue inhibitor of metalloproteinase 3 ( Timp3 )) was reported, as well as and down-regulation of cytoskeletal genes (alpha actin cardiac 1 ( Actc1 ), beta actin ( Actb ), Tropomyosin 4 ( Tpm4 )), checkpoint genes (cyclin D1 ( Ccnd1 ), cyclin D2 ( Ccnd2 )) (Gilmour et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…When rats were fed a high zinc diet (347.50 mg Zn/kg basis diet, compared to a normal diet level of 35.94 mg Zn/kg basis diet), up-regulated genes included those involving carbohydrate metabolism (e.g. alcohol dehydrogenase ( Adh5) , pyruvate dehydrogenase kinase 4 ( Pdk4) , aldolase C ( Aldoc) ) (Sun et al, 2007). Another study utilizing intratracheal instillation of zinc sulfate in rats was focused on changes in cardiac gene expression, where up-regulation of respiratory/mitochondrial function genes (pyruvate dehydrogenase kinase 4 ( Pdk4 ), acylcoenzyme A dehydrogenase ( Acadvl )), injury/stress response (heme oxygenase 1 ( Hmox1) , tissue inhibitor of metalloproteinase 3 ( Timp3 )) was reported, as well as and down-regulation of cytoskeletal genes (alpha actin cardiac 1 ( Actc1 ), beta actin ( Actb ), Tropomyosin 4 ( Tpm4 )), checkpoint genes (cyclin D1 ( Ccnd1 ), cyclin D2 ( Ccnd2 )) (Gilmour et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is required for the normal growth and development of all animal species including humans, and its deficiency results in a reduced growth rate [24][25][26][27] . The current results also showed that zinc deficiency caused remarkable reductions in the body weight of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary factors including glucose, fructose, vitamin A, cholesterol, vitamin D, polyunsaturated fatty acids, alcohol and conjugated linoleic acid are known to regulate SCD gene expression [reviewed by Ntambi and Miyazaki (2004)]. Excess iron (Fe) increases the SCD gene expression in the liver of mouse (Pigeon et al., 2001), while zinc (Zn) decreases the gene expression in the liver of rats (Sun et al., 2007). Recently, studies have demonstrated that Cobalt (Co) reduces the proportion of stearoyl‐CoA desaturated fatty acids in milk when supplied in large amounts in both dairy cows (Shingfield et al., 2008; Taugbøl et al., 2008, 2010) and lactating sows (Karlengen et al., In press).…”
Section: Introductionmentioning
confidence: 99%